Population aging in Korea: Importance of elderly workers - Jaejoon Lee (KDI Journal of Economic Policy, 2023)
Korea's population is aging at a faster pace than any other major country, and the adverse impact of this trend on the economy is predicted to be significant. This paper focuses on the macroeconomic effects of population aging with particular attention paid to the pace of aging in Korea. According to our analysis, it is difficult to offset the decline in the labor supply driven by rapid population aging, even if the labor force participation rate of the working-age population rises to a significantly high level. We suggest a re-orientation of policy directions to correspond to the behavioral changes of economic agents. Policies must focus on promoting labor force participation among the elderly while pushing towards human capital advancement and higher productivity.
Keywords: J11; E66; 330; Korean Economy; Population Aging; Economic Growth